Students' perceptions of Android-based digital textbooks in higher education - Pahlevi, Triesninda; Ranu, Meylia Elizabeth; Nugraha, Jaka (Indonesian Journal of Educational Development (IJED), 2025)
The urgency of this research is that the development of Android-based digital textbooks for Electronic Records Management courses is urgently needed to support the OBE curriculum, improve 21st-century skills, and facilitate interactive and accessible learning. This research aimed to measure students' perceptions to develop an Android-based digital textbook for the Electronic Records Management course to support the implementation of Outcome-Based Education (OBE) in higher education. Utilising the 4D development model, Define, Design, Develop, and Disseminate, the study involved 60 students from the Office Administration Education program at a state university in East Java. Validation by experts in content, media, and language resulted in scores of 92.83%, 95.65%, and 86%, respectively, indicating a high feasibility level. Student responses were overwhelmingly positive, with mean scores exceeding 4.21 across categories such as format, relevance, engagement, satisfaction, and confidence. The findings confirm the digital textbook's effectiveness in enhancing 21st-century skills and meeting learning outcomes aligned with OBE standards. Recommendations include refining visual elements and adding interactive features to maintain engagement. This research contributes significantly to digital textbook development, emphasising accessibility and adaptability to meet the demands of modern education and professional readiness.